El Excentrico, 1956-07-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
July 20, 1956 [20 de julio de 1956]. Ano 6, No 22. Cover contains a photo of Margo Najera, who was a winner of the 1956 C.S.O. Beauty Contest.